Understanding the impact loading characteristics of a badminton lunge among badminton players - Lam, W.-K.; Lee, K.-K.; Park, S.-K.; Ryue, J.; Yoon, S.-H.; Ryu, J. (PLOS ONE, 2018)
The rapid and repetitive badminton lunges would produce strenuous impact loading on the lower extremities of players and these loading are thought to be the contributing factors of chronic knee injuries. This study examined the impact loading characteristics in various groups of badminton athletes performing extreme lunges. Methods: Fifty-two participants classified into male skilled, female skilled, male unskilled, and female unskilled groups performed badminton lunge with their maximum-effort. Shoe-ground kinematics, ground reaction forces, and knee moments were measured by using synchronised force platform and motion analysis system. A 2 (gender) x 2 (skill-level) factorial ANOVA was performed to determine the effects of different gender and different playing levels, as well as the interaction of two factors on all variables. Results: Male athletes had faster approaching speed (male 3.87 and female 1.08 m/s), longer maximum lunge distance (male 1.47 and female 1.16 m), larger maximum (male 215.7 and female 121.65 BW/s) and mean loading rate (male 178.43 and female 81.77 BW/s) and larger peak knee flexion moment (male 0.75 and female 0.69) compared with female athletes (P < 0.001). Unskilled athletes exhibited smaller footstrike angle (skilled 45.78 and unskilled 32.35°), longer contact time (skilled 0.69 and unskilled 0.75 s), larger peak horizontal GRF (skilled 1.61 and unskilled 2.40 BW), smaller mean loading rate (skilled 150.15 and unskilled 110.05 BW/s) and larger peak knee flexion moment (P < .05; skilled 0.69 and unskilled 0.75 Nm/BW) than the skilled athletes. In addition, the interaction indicated greater peak GRF impact in female unskilled athletes compared with female skilled athletes (P < 0.001; female skilled 2.01 and female unskilled 2.95 BW), while there was no difference between male participants (P > 0.05; male skilled 2.19 and male unskilled 2.49 BW). Conclusions: These data suggested that male athletes and/or unskilled athletes experience greater impact loading rates and peak knee flexion moment during lunge compared with female and skilled athletes, respectively. This may expose them to higher risk of overuse injuries. Furthermore, female unskilled athletes seemed to be more vulnerable to lower extremity injuries.